Health Determinants of Physical Conditions of Homes Incidence of Pulmonary TB in the Nganjuk Community Health Center Working Area Year 2020 - Sherly Novalia Rahmawati; Setyo Budi Susanto (Journal of Hospital Management and Services, 2021)
Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium tuberculosis) Houses that do not meet health requirements are one of the risk factors for pulmonary tuberculosis. This study aims to analyze the factors of physical conditions of houses against the incidence of pulmonary TB in the Nganjuk health center work area in 2020.This study is a type of analytical survey research with a case-control study design . The population in this study were patients with pulmonary TB and non-patients with pulmonary TB totaling 82 people. The sampling technique used total sampling. Data analysis used logistic regression analysis.The results of the study showed that the physical condition of the house that influenced the incidence of TB in the Nganjuk Health Center work area was ventilation with a significant value of 0.002 with an R odd value = 1.424.